COVID-19 and hearing loss—A narrative review - Feng, Sharon J.; Voruz, François; Yu, Michelle; Lalwani, Anil K. (Frontiers in Audiology and Otology, 2023)
Interest in hearing loss associated with COVID-19 has increased since the pandemic started. Early on during the spread of SARS-CoV-2 across the globe, reports of smell and taste disorders secondary to COVID-19 emerged, and to a lesser extent, reports of sensorineural hearing loss also surfaced. This raised questions regarding changes in the epidemiology of hearing loss and modifications to otologic practice that have evolved in response to the COVID-19 pandemic. To elucidate these questions, we performed a comprehensive literature search, including articles up to November 2022, using “COVID hearing loss” in MEDLINE. A total of 153 articles were included for full-text review and data extraction. There are several proposed mechanisms through which COVID-19 may contribute to hearing loss—direct viral infection, microthrombi, or hemorrhage. There is a growing repository of case reports and series on SARS-CoV-2-associated sensorineural hearing loss, with variable quality. Most patients who experienced hearing loss did so within a month of infection, with most patients' symptoms resolving within 2 weeks. The growing body of literature discussing SARS-CoV-2-associated hearing loss does not suggest a significant rise in the occurrence of sensorineural or overall hearing loss. In this ongoing COVID-19 era, hearing loss should be approached in the same state-of-the-art manner as before the pandemic.